2016
DOI: 10.1002/prca.201600041
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry methods for predicting antibiotic resistance

Abstract: Developing elaborate techniques for clinical applications can be a complicated process. Whole-cell MALDI-TOF MS revolutionized reliable microorganism identification in clinical microbiology laboratories and is now replacing phenotypic microbial identification. This technique is a generic, accurate, rapid, and cost-effective growth-based method. Antibiotic resistance keeps emerging in environmental and clinical microorganisms, leading to clinical therapeutic challenges, especially for Gram-negative bacteria. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 138 publications
(177 reference statements)
0
35
0
Order By: Relevance
“…Mass spectrometry methods for the direct detection of OXA-48 carbapenemases have been proposed, but the detectability, relative abundance, and spectral characteristics of specific peptides common to the OXA-48 family remain to be characterized (18). Given the value of rapid diagnostic methods for antimicrobial resistance detection, we sought to evaluate liquid chromatography-tandem mass spectrometry (LC-MS/MS) as a technique for the direct detection of OXA-48 family carbapenemases.…”
mentioning
confidence: 99%
“…Mass spectrometry methods for the direct detection of OXA-48 carbapenemases have been proposed, but the detectability, relative abundance, and spectral characteristics of specific peptides common to the OXA-48 family remain to be characterized (18). Given the value of rapid diagnostic methods for antimicrobial resistance detection, we sought to evaluate liquid chromatography-tandem mass spectrometry (LC-MS/MS) as a technique for the direct detection of OXA-48 family carbapenemases.…”
mentioning
confidence: 99%
“…LC-MS/MS revealed that several of the carbapenem resistant isolates produce no detectable OprD porin, which is produced at wild-type levels in the carbapenem susceptible, AmpC hyperproducing isolate 73-56826 (Table 5). The involvement of AmpC hyperproduction, MexAB-OprM hyperproduction and OprD downregulation in cephalosporin and carbapenem resistance in P. aeruiginosa clinical isolates are all well-known phenomena [29], but each is under complex control [30], and so currently it is not possible to predict abundance for these proteins based solely on WGS [14] and P. aeruginosa is considered very challenging even for proteomics based antimicrobial susceptibility prediction [17]. Our LC-MS/MS methodology shows that it is possible to achieve.…”
Section: Resultsmentioning
confidence: 99%
“…This has the potential to give both identification and abundance data that might resolve many of the uncertainties surrounding the use of WGS. This has recently been reviewed, and, whilst there have been some successes identifying some ABR proteins in some cases, a methodology to allow whole proteome analysis that can accurately quantify ABR proteins, which can be used to accurately predict antimicrobial susceptibility is yet to be demonstrated [17]. We have been using so called “shotgun” proteomics via a nano-liquid chromatography, Orbitrap tandem mass spectrometry approach to characterise proteomic responses to mutations in regulators that affect ABR [16,18].…”
Section: Introductionmentioning
confidence: 99%
“…However, a potential limitation of these approaches is that they are indirect. A more direct approach that uses MS to detect tryptic peptides of carbapenemases has been suggested 24 , and a variety of related methods have been studied 25 . A shotgun proteomics-based method using microwave-assisted tryptic digestion followed by liquid chromatography (LC)-nano-electrospray ionization trap MS identified OXA-family beta-lactamases and the carbapenem-resistance associated CarO protein from Acinetobacter baumannii 26 , and a method based on capillary electrophoresis-electrospray ionization(CE-ESI) MS/MS was able to identify tryptic peptides of KPC and OXA-48 carbapenemases from cultured isolates reliably for accurate classification 27 .…”
Section: Introductionmentioning
confidence: 99%